Green and Ethanol‐Resistant Polyurethane Nanofibrous Membranes Based on an Ethanol Solvent for Waterproof and Breathable Textiles. (25th June 2020) - Zhou, Wen; Yu, Xi; Cao, Leitao; Yang, Ming; Li, Yang; Si, Yang; Yu, Jianyong; Ding, Bin
Abstract: Waterproof and breathable (W&B) membranes can resist liquid water penetration while transmitting water vapor simultaneously, which is critical for improving the comfort and protection offered by the resulting textiles; however, it remains a substantial challenge to construct promising nontoxic W&B membranes based on green solvents. Here, a simple and scalable strategy is developed for fabricating green, W&B, polyurethane nanofibrous membranes based on an ethanol solvent via emulsion electrospinning and post thermal treatment. A novel ethanol‐soluble and spinnable polyurethane is synthesized by a stepwise polymerization reaction. Notably, green nanofibrous membranes with high hydrophobicity are obtained based on fluorinated polyurethane/ethanol emulsions, utilizing the synthesized polyurethane as the template polymer. Furthermore, the introduction of the aziridine crosslinker (tris (2‐methyl‐1‐aziridine propionate) (TTMA)) constructs the structure by post thermal treatment between TTMA and ethanol‐soluble polyurethane, resulting in the exceptional ethanol resistance of the nanofibrous membranes. The resulting membranes present integrated functionalities of a robust hydrostatic pressure of 86.2 kPa, high water vapor permeability of 13.1 kg m −2 d −1, good air permeability of 5.5 mm s −1, low mass‐loss rate of 8.6 wt% after 60 min ethanol immersion, and desirable elasticity with a strain recovery ratio of 79.2%, offering strong potential for the next generation green and nontoxic protective textiles. Abstract : A simple and scalable strategy for constructing green, waterproof, and breathable polyurethane nanofibrous membranes using ethanol as a solvent is proposed. Herein, a novel ethanol‐soluble and spinnable polyurethane is synthesized via a stepwise polymerization route. The membranes are endowed with good hydrophobicity and ethanol resistance by introducing the fluorinated polyurethane and aziridine crosslinker via emulsion electrospinning and thermal crosslinking.